Triagem de dor neuropática em indivíduos com doença falciforme: aplicação de apenas uma ferramenta é suficiente? - Antunes, Fabricio Dias (2019)
Introduction: Sickle cell disease is one of the most common haematological pathologies worldwide and is associated with several acute complications with well-stabilized therapy. On the other hand, conditions are painful as a neuropathic pain. Objectives: To identify the best tool for neuropathic pain´s screening in patients with sickle cell disease. To compare neuropathic pain assessment instruments: Neuropathic pain questionnaire (NPQ), Douleur Neuropathique en 4 Questions (DN-4), Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) e painDetect Questionnaire (PDQ). To validate the NPQ tool in Portuguese. To characterize the clinical and epidemiological profile of neuropathic pain in patients with sickle cell disease. Method: Before using any tool to detect neuropathic pain, a translation of the NPQ was requested for portuguese language closely related to the criteria established in the literature. Out of a total of 554 patients with sickle cell disease at the outpatient clinic of the University Hospital of the Federal University of Sergipe, 103 patients attended the criteria for dismissal (Symptomatic Sickle cell disease confirmed by hemoglobin electrophoresis, age equal to or greater than 14 years, absence of pain crisis and hemotransfusion in the last month, and no other organic pathology diagnosed prior to this study) and they answered all the tools at first moment. As a methodology for the validation of diagnostic tools, a second moment corresponding to one year was necessary for the application of NPQ again. This time, after considering losses due to absence from the outpatient clinic or not meeting the inclusion criteria, 41 patients, out of 103 cited above, answered the NPQ. As the sample size calculated was 40 patients, the number of 41 patients obtained in the second time of the research was adequate. So the analyzes and comparisons could be made to achieve the objectives. Pearson correlation and Spearman correlation were used in the comparison between the evaluation tools or in the validation. Comparisons between groups were done using Chi-Square/Fisher's exact test or t test/Mann-Whitney. Results: The best way to screen for neuropathic pain in individuals with sickle cell disease is the combination of tools rather than their use alone. DN-4, LANSS and PDQ together, tools already validated in Portuguese, detected the highest number of patients with neuropathic pain among those with sickle cell disease with a prevalence of 50.4%. The comparison between instruments of this research with the purpose of measuring the similarity between them demonstrated a low equivalence and this reinforces the theory that more than one neuropathic pain detection tool is necessary in order to avoid unnecessary losses of false negative patients. There was no homogeneity and stability with the NPQ instrument in the portuguese language in this group of patients with sickle cell disease, making it impossible to validate the NPQ tool. The clinical and epidemiological profile of this group with neuropathic pain usually consists of older people with very characteristic sensorial alterations, distributed homogeneously by sex, with localized pain mainly lumbar and without therapeutic approach until the moment.